Lessons and Insights from the Wimbledon Championships for China’s Professional Tennis Tournaments - Zhang, Wentao (Transactions on Social Science, Education and Humanities Research, 2024)
As tennis continues to grow, China's professional tournaments are emerging yet face numerous challenges. This paper employs documentary research and logical analysis to examine Wimbledon's operational strategies, offering insights for domestic tournament organization. Findings highlight Wimbledon's success in fostering a strong tournament culture and heritage, maintaining a balance between non-commercial values and global strategies, and leveraging new technologies for enhanced analytics and service expansion. For China's professional tournaments, it is recommended to develop a distinct brand culture, integrate local characteristics and combine traditional values and commercials, optimize revenue structures, and utilize smart technologies for upgrades and comprehensive system improvements, thus enhancing their international competitiveness.